A comparative methodological approach for the calculation of ships air emissions and fuel-energy consumption in two major Greek ports. Issue 8 (17th November 2022) - Doundoulakis, Emmanouil; Papaefthimiou, Spiros
ABSTRACT: The scope of the paper is to focus on the main technical discrepancies, that is, engine load factor (LF), specific fuel oil consumption (SFOC), emissions factors (EF), included in the existing methodological approaches for calculating ships' on-board emissions and propose a framework that will allow various stakeholders to conduct accurate air emissions calculations based on publically available operational data. A bottom-up methodology has been employed for the calculation of fuel-energy consumption and air emissions (CO2, SOx, NOx, PM10 ) in two major ports (Souda and Heraklion) of Crete island in Greece for passenger ferries and cruise ships for the years 2018 and 2019 and for both main and auxiliary engines of all vessels. Due to the lack of publically available technical data, the proposed methodology is based on the estimation of SFOC values through a regression analysis that leads to accurate and reliable results. The basic scenario is based on a detailed estimation of SFOC via a regression analysis applied on engine's technical data, while the alternative approaches employ SFOC estimated through the application of specific adjustment factors and main engine power based on ship's gross tonnage. The basic scenario results are the most accurate data while in most other cases air emissions are underestimated observing significant differences between the different methodologies.